The Influence of Non-Performing Loans, Internal Rate of Return, Capital Adequacy Ratio and XYZ Bank Stock Price on XYZ Bank Performance - Indra Wahyu Putra, Christophorus (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of financial management. The literature review research article on the influence of non-performing loans, internal rate of return, capital adequacy ratio and XYZ bank stock price on XYZ bank performance is a scientific literature article in the scope of financial management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Non-performing Loans affect XYZ Bank Performance; 2) Internal Rate of Return affects XYZ Bank Performance; 3) Capital Adequacy Ratio affects XYZ Bank Performance; and 4) Bank XYZ's share price affects Bank XYZ's performance.